Multidisciplinary analysis of 3D seismotectonic modelling: a case study of Serre and Cittanova faults in the southern Calabrian Arc (Italy) - Giuffrida, S.; Brighenti, F.; Cannavò, F.; Carnemolla, F.; De Guidi, G.; Barreca, G.; Gambino, S.; Barberi, G.; Scarfì, L.; Monaco, C. (Frontiers in Earth Science, 2023)
Active normal faulting and uplifting, consistent with a WNW-ESE oriented regional extension, dominate the Quaternary tectonics of the southern Calabrian Arc. The main tectonic structures of this extensional domain are considered to be the source of numerous historical and recent strong earthquakes, among which the 1783 seismic sequence (M 6.5-7) was one of the most destructive ever recorded in Southern Italy. Previous works on the seismotectonic of the Calabrian Arc indicate a disagreement on the attitude (E-dipping vs W-dipping) of the main seismogenic sources slicing across Southern Calabria, whereby the seismotectonic framework remains still debated. Following a multidisciplinary approach, based on morpho-structural and seismological data, the geometry at depth of the most reliable sources (i.e., Cittanova and Serre faults) was firstly modeled in a 3D environment to retrieve information about their seismic potential. GNSS data of the permanent stations of RING/RDN and TopNetlive Italy networks have been processed in order to estimate the velocity field affecting this area. Then, data the inversion allowed us to document a predominant WNW-ESE active extensional strain orthogonally to the modelled faults, consistent with the regional dynamics. The reliability of the model was tested using empirical relation and fault response modeling simulation. Furthermore, Slip Tendency analysis revealed the propensity to slip of the modelled planes by applying a remote stress state derived from the kinematic-structural survey on fault planes.